THE INFLUENCE OF INCENTIVE/REWARD SYSTEM AND MOTIVATION ON EMPLOYEES WORK ACHIEVEMENT ON PT. ASURANSI JIWASRAYA (PERSERO) SOUTHMEDAN BRANCH - Novia Ruth Silaen; Jenni Tarigan; Risnawati Siregar (Lembaga Penelitian dan Pengabdian Masyarakat Universitass Darma Agung, 2020)
This study aims at determining whether the system of rewards and motivation affect the work performance of employees at PT. Asuransi Jiwasraya (Persero) Medan. The hypothesis is the reward and motivation system influences employee work performance. The population is all employees, amounting to 35 people with a sample of 35 people. The analytical method is the analysis of Multiple Linear Regression, t-test, F-test and Determination test. The results of this study indicate that the equation of Multiple Linear Regression Y = 0.615 + 0.666X1 + 0.572X2, which means that the reward and motivation system has a positive effect on employee performance. Based on the t-test showed a positive and significant effect, it was seen that the significance for the effect of X1 on Y was 0.010 < 0.05, tvalue 2.732> ttable 2.037. The effect of X2 on Y is 0.001 < 0.05, tcount value of 3.763 > ttable 2.037, which means that if the reward and motivation system is improved then the employee's work performance will increase. Based on the F test shows that the reward and motivation system simultaneously and significantly influence employee performance where Fcount 70.548 > Ftable 3.29, and the significance value (0.000 < 0.05). And the results of the coefficient of determination test on Adjusted Rsquare of 0.804 which means that the reward and motivation system is able to explain the increase in employee performance by 80.4% the remaining 19.6% is explained by other variables.